Thai population data on nine tetrameric STR loci - D3S1358, vWA, FGA, TH01, TPOX, CSF1PO, D5S818, D13S317 and D7S820 - Wasun Chantratita (2018)
Allele frequencies for the nine STR loci included in the AmpFlSTR Profiler kit were determined in a Thai population of 100 unrelated individuals. (C) 2001 Elsevier Science Ireland Ltd.